The Effect of Augmented Reality (AR) Media on Improving The Speaking Skills of Elementary School Students - Nazwa Nurul Adzkiya; Fikriyah Fikriyah; Fanny Septiany Rahayu (FKIP - Universitas Riau, 2026)
Speaking skills are among the essential language competencies that elementary school students must master. However, the initial level of fifth grade students at Majasem 2 Public Elementary School indicates that their speaking skills are still relatively low, with an average score of 41.75 on the pretest. Students still struggle to pronounce words correctly, use appropriate intonation, choose suitable vocabulary, speak fluently, and express their ideas and opinions confidently during the learning process. This study aims to determine the effect of using Augmented Reality (AR) media on improving the oral skills of fifth grade students at Majasem 2 Public Elementary School. This study employs a quantitative approach using a pre-experimental method and a “One-Group Pre-Test/Post-Test” research design. The sample consisted of 20 students selected through purposive sampling. Data were collected through oral expression tests, observations, and documents. The research instruments met the criteria for validity and reliability (Cronbach’s alpha coefficient = 0.873). Data analysis was conducted using the Shapiro-Wilk normality test, the Wilcoxon signed-rank test, and N-Gain analysis, using IBM SPSS software version 25. The results showed a significant difference between pre-test and post-test scores (asymptotic significance = 0.000 < 0.05). Furthermore, the average N-Gain score of 0.6781 fell into the “moderate” category. Thus, Augmented Reality (AR) media has a positive impact on improving the speaking skills of elementary school students.